Daniel Tiger's neighborhood. Family fun collection [videorecording (DVD)] - Santomero, Angela C. (PBS, 2018)
There's time for family fun all year round with Daniel Tiger! Watch Daniel and his dad work together to build a playhouse and then take a special fall walk through the neighborhood, where they admire the colors of the leaves along the way. Next, the entire Tiger family heads out on a road trip to Grandpere's house, where they learn all about the exciting things to do and see when on a family trip.